Pendampingan Menulis Huruf Hijaiyah Sebagai Upaya Meningkatkan Kecintaan Anak Pada Alquran di Mushola Al-Ikhlas Pakalongan Sampang - Arofiq Arofiq; Nelud Darajatul Aliyah (Jurnal Pelayanan Masyarakat, 2024)
This activity aims to develop and advance religious education in the ability to write hijaiyah letters and increase children's love for the Koran at the Al Ikhlas Pakalongan Musholla. This service uses the PAR method, namely a method where the teacher gives special tasks so that students carry out activities by practicing. In an effort to optimize students' skills and also based on phenomena that occur in the local community in teaching the Qur'an. Students can also utilize their free time or free time with productive activities which are also useful for increasing their ability to write hijaiyah letters. This service activity produced several results, namely: increasing students' skills or expertise in writing the Koran, increasing knowledge of hijaiyah letters, and students being able to pronounce hijaiyah letters well. Learning hijaiyah letters is very important to maintain scientific truth, obey the teachings of the Prophet Muhammad and protect the language so that reading errors do not occur.